Class-Based Assessment Concepts: A Comprehensive Study - Nurhuda, Abid; Setyaningtyas, Nur Aini; Huda, Ali Anhar Syi’bul (Advances in Humanities and Contemporary Studies, 2024)
The assessment carried out by educators on students must be comprehensive and include cognitive, affective, and psychomotor aspects and cannot be looked at from one side only, besides that, it also has certain concepts. One form of the many assessment concepts that can be carried out by educators is class-based assessment. So the purpose of this study is to describe the Class-Based Assessment Concept. This research uses descriptive qualitative techniques with a literature study approach model. The results of the study show that the Class-Based Assessment Concept aims to find detailed information about student learning outcomes. And principled in validity, education, competency-oriented, fair, objective, open, sustainable, comprehensive, and meaningful. So with all that, if there are students who still have not finished their studies, remedial can be done which functions to heal, as well as adaptive, interactive, flexible principles, there is feedback, continuity, and availability in providing services. Then in developing the implementation the educator must explain the material again, students must study independently, then retest, give additional assignments, study groups with teacher guidance, and finally study groups with the guidance of students who have graduated from their studies.